Mediating role of entrepreneurial intention on the relationship between entrepreneurship education and employability: a study on university students from a developing country - Md. Abu Issa Gazi; Md. Kazi Hafizur Rahman; Mohd Faizal Yusof; Abdullah Al Masud; Md. Aminul Islam; Abdul Rahman bin S. Senathirajah; Md. Alamgir Hossain (Cogent Business & Management, 2024)
This study assesses how entrepreneurship education influences the entrepreneurial intentions and employability of students. It also investigates the mediation effect of entrepreneurial intentions on the relationship between entrepreneurial education and employability, as well as the direct effects on employability. In this research, a quantitative method was used to gather data from 397 university students through a survey questionnaire measured on a seven-point Likert scale using a convenience sampling method. We utilized structural equation modeling (SEM) to examine the data. A CMV model was used to evaluate the model's fitness, validity, reliability and of the data, and an SEM technique was used to test the hypotheses. The study found that entrepreneurship education could boost students' employability as well as their desire to start their own businesses. It shows how important entrepreneurship education is for learning the skills and knowledge needed to start a business. The study also suggests that having entrepreneurial intentions can enhance one's employability. This study reveals a heightened understanding of how entrepreneurship education impacts on entrepreneurial intention and employability. These insights can guide improvements in entrepreneurship programs to align with local employment needs. Moreover, the identified mediator, entrepreneurial intentions, presents a targeted opportunity for intervention, suggesting practical ways to cultivate entrepreneurial skills and mindset, ultimately enhancing employability prospects in the region.Unlocking the doors to career success and personal enterprise, our study delves into the transformative power of entrepreneurship education. We discovered that not only does such education enhance employability among students, but it ignites a passion for entrepreneurship itself. Picture a world where learning to start your own business not only opens doors to self-employment but also boosts your overall job prospects. Our findings shed light on the vital role entrepreneurial intentions play in this journey, offering a roadmap for educators and policymakers to refine programs that not only meet local employment needs but also foster a mindset of innovation and empowerment. Join us in envisioning a future where education becomes the key to unlocking both traditional job opportunities and the entrepreneurial spirit within us all.
Keywords: 650; Education; starting entrepreneurs; entrepreneurial skills; entrepreneurial intention; employability